The crosstalk of CD8+ T cells and ferroptosis in cancer - Lin, Zhengjun; Zou, Songzhu; Wen, Kunming (Frontiers in Immunology, 2024)
Ferroptosis is an iron-dependent, novel form of programmed cell death characterized by lipid peroxidation and glutathione depletion and is widespread in a variety of diseases. CD8+ T cells are the most important effector cells of cytotoxic T cells, capable of specifically recognizing and killing cancer cells. Traditionally, CD8+ T cells are thought to induce cancer cell death mainly through perforin and granzyme, and Fas-L/Fas binding. In recent years, CD8+ T cell-derived IFN-γ was found to promote cancer cell ferroptosis by multiple mechanisms, including upregulation of IRF1 and IRF8, and downregulation of the system XC-, while cancer cells ferroptosis was shown to enhance the anti-tumor effects of CD8+ T cell by heating the tumor immune microenvironment through the exposure and release of tumor-associated specific antigens, which results in a positive feedback pathway. Unfortunately, the intra-tumoral CD8+ T cells are more sensitive to ferroptosis than cancer cells, which limits the application of ferroptosis inducers in cancer. In addition, CD8+ T cells are susceptible to being regulated by other immune cell ferroptosis in the TME, such as tumor-associated macrophages, dendritic cells, Treg, and bone marrow-derived immunosuppressive cells. Together, these factors build a complex network of CD8+ T cells and ferroptosis in cancer. Therefore, we aim to integrate relevant studies to reveal the potential mechanisms of crosstalk between CD8+ T cells and ferroptosis, and to summarize preclinical models in cancer therapy to find new therapeutic strategies in this review.